Pola Pembinaan Sikap Tawadhu' Peserta Didik Di MA Matholiul Anwar Simo Lamongan - Rahmat Surya Alam Aljihadi; Siti Suwaibatul Aslamiyah; Ahmad Hanif Fahruddin; Moch Faizin Muflich (Akademika, 2022)
This research is entitled Patterns of Fostering Tawadhu Attitudes of Students at MA Matholiul Anwar Simo Karanggeneng Lamongan. This study uncovers problems in the character of each student who is currently experiencing a decline, the purpose of this research is to find out the pattern of fostering the attitude of humility of students to educators at MA Matholiul Anwar Simo Karanggeneng Lamongan. This research uses qualitative research and a phenomenological approach. The results of this study, the first is the pattern of implementing the development of the tawadhu attitude of students in learning at MA Matholiul Anwar Simo. And the second is related to the process of fostering the humble attitude of students in everyday life at MA Matholiul Anwar Simo. The supporting factor in this program is the important battle of various supporting elements to realize the personality characters of students to be better and useful in the community. While the inhibiting factors in this program lie in various internal and external factors that affect the students themselves whose level of development of thinking patterns is still easily shaken by things that are vague. To overcome these inhibiting factors is through efforts to develop the character of students (tawadhu) patiently and continuously.